POTENSI ADOPSI TEKNOLOGI RESIRKULASI AKUAKULTUR (RAS) SKALA RUMAH TANGGA DALAM PENGGEMUKAN KEPITING, TANTANGAN DAN PELUANG BAGI PETANI TAMBAK TRADISIONAL DESA PULOKERTO PASURUAN - Arifin, Moh. Zainal; Widodo, Agus; Nazran, Nazran; Surakhmad, Djoko; Sugeng Rahardjo; Dewi Alima Nostalia Suseno (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2025)
This quantitative research draws on secondary data from companies listed on the Indonesia Stock Exchange, specifically targeting the Food and Beverages Subsector over the 2018–2022 period. Using purposive sampling, the study gathered data from 20 companies, resulting in a total of 294 observations covering the variables ROE, AGR, and PBV. The analysis, performed with SEM-PLS using SmartPLS 4, indicates that AGR does not have a significant direct relationship with PBV, suggesting that company growth, as measured by AGR, has a limited effect on the increase in firm value. In contrast, ROE demonstrates a strong and positive impact on company value, highlighting the importance of improving profitability to enhance overall firm worth. These results stress the managerial importance of focusing on strategies that boost profitability, as it is closely tied to company valuation and investor interest. Furthermore, the study points out that companies must remain responsive to external factors, such as regulatory shifts and changing consumer behavior, which may play a more critical role in shaping and increasing firm value than internal growth indicators alone.